(untitled) (Research, Society and Development, 2022)
Objective: To describe the incidence of clinical conditions and the demographic profile of patients treated by the Mobile Emergency Care Service (SAMU), for traumatic reasons, in the city of Belém do Pará, in February and March 2016. Methodology: Cross-sectional study, quantitative and descriptive, having as source the attendance records of the SAMU of Belém do Pará. Only those that had identification of the reasons for the trauma of patients treated by the SAMU of the city of Belém, in February and March 2016, were included. Result: 944 records of accidents due to external causes were analyzed during the study period. As for clinical conditions, most patients had pressure values ​​above normal (49.9%), awake (62.4%), with oxygen saturation between 95 and 99% (52.3%), heart and respiratory rates within the normal range (75.6% and 47.9%, respectively) and with lesions in multiple body segments (26.9%). The most affected age group and sex were, respectively, 20 to 59 years old (71%) and males (66.9%). As for the level of consciousness, most men (12.8%), aged between 20 and 59 years (10%), were found to be drunk. The most prevalent reason for triggering was due to traffic accidents, which predominated in both sexes (50.8%) and in the age group from 20 to 59 years (74%). Conclusion: This reality found reinforces the need for dissemination of preventive measures capable of reducing the number of incidents, by government authorities on education, for example, in traffic, in schools, churches.